Implementation of financial management and digital marketing to increase the business competitiveness of the SMEs of Skin Cracker 'Tiga Berlian' - Maimunah Maimunah; Heru Yusmanto; Devara Avila Sebastian; Daffa Syahnakri Mikola Rusadi; Henni Lestari; Salsabila Putri Abhiseka (Universitas Muhammadiyah Magelang, 2022)
The rapid development of technology in the digital world and the internet has an impact on the world of marketing. One of the problems with the low competitiveness of SMEs is the limited ability of businessman in doing marketing. This community service was carried out to introduce skin cracker ‘Tiga Berlian’ products to a wider market and increase business competitiveness through the digital marketing. The method used is to provide training and assistance to SME entrepreneurs. This activity is carried out over a period of approximately 1 month. The outputs of the activities that have been carried out are the skin cracker ‘Tiga Berlian’ website, financial reports and account creation in the marketplace. The community service can provide increased partner skills regarding the concept of digital marketing and financial report management, so that they can support increased sales and increase the competitiveness of SMEs.